Pengaruh Brand Image, Product Quality dan Brand Trust Terhadap Keputusan Pembelian Produk Skincare Skintific (Studi pada Mahasiswa Kota Malang) - Nissa, Uswatul Tirania Choirul; Alrasyid, Harun; Efendi, Erfan (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research aims to analyze and explain the effect of brand image, product quality and brand trust on purchasing decisions for skincare products among Malang City students. This study employs a quantitative approach, untilizing the Maholtra formula to determine the sample size due to the uncertainty surrounding the population size. Based on the result of the Maholtra formula, the sample size was 105 respondents. To solve the problem in this study, SPSS 24 was used to analyze various tests, such as validity, reliability, and adjusted R² determination coefficient tests. The results show that brand image, product quality and brand trust influence purchasing decisions. Brand image, product quality and brand trust significantly affect purchasing decisions. Keywords: Brand Image, Product Quality, Brand Trust, Purchase Decision